Analisis Penerimaan Pajak dan Retribusi Kota Medan Serta Hubungannya dengan Pelayanan Publik di Kota Medan dalam Meningkatakan Taraf Hidup Masyaratkat Kota Medan dari Segi Ekonomi - Purba, Erni Susilawati; Simarmata, Kristin Margaretha; Nurlianti, Sofiah; Lubis, Putri Kemala Dewi (As-Syirkah: Islamic Economic & Financial Journal, 2024)
The aim of this research is to determine and analyze the growth of PAD (Regional Original Income) in Medan City at the Medan City Regional Tax and Levy Management Agency and to determine the influence of Tax and Levy Revenue on Public Services in Medan City. This research uses a descriptive single case study approach, which aims to collect, compile, classify and interpret data to provide an accurate picture of the nature of individuals, groups, conditions and symptoms in a society. Research results from the Regional Tax and Levy Management Agency for Medan City, the Ministry of Finance, and literature studies show that tax and levy revenue in Medan City has not reached the target for the last three periods. Public services in Medan City have experienced a significant decline, influenced by poor budget factors in revenue and allocation, as seen from the decline in Regional Original Income (PAD) over the last three years.